2012
DOI: 10.1159/000342213
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Physical Fitness and Daily Energy Expenditure on Sleep Efficiency in Young and Older Humans

Abstract: Background: Physical activity is known to influence sleep efficiency. Relatively little is known about the relationship between physical activity and sleep efficiency in young and older humans and the impact of exercise training on sleep efficiency in healthy older individuals. Objectives: To determine the relationship between physical fitness and daily energy expenditure with sleep efficiency in young and older subjects, and assess the effect of 12-month exercise training on sleep efficiency in healthy older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 89 publications
2
48
0
Order By: Relevance
“…The older sample in our study demonstrated a larger range in MVPA than young, which may have led to the observation of a stronger relationship with sleep quality in this group. Previous research has shown that increasing fitness, while maintaining daily energy expenditure in older adults was not associated with changes in sleep quality (Oudegeest-Sander et al , 2013). Taken together with the results of the present study, it is suggested that habitual physical activity levels, rather than fitness, are associated with sleep quality in older adults.…”
Section: Discussionmentioning
confidence: 98%
“…The older sample in our study demonstrated a larger range in MVPA than young, which may have led to the observation of a stronger relationship with sleep quality in this group. Previous research has shown that increasing fitness, while maintaining daily energy expenditure in older adults was not associated with changes in sleep quality (Oudegeest-Sander et al , 2013). Taken together with the results of the present study, it is suggested that habitual physical activity levels, rather than fitness, are associated with sleep quality in older adults.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, while the average level of physical activity did not predict sleep quality, fluctuations in sleep quality did predict subsequent sleep quality. Previous research has revealed that exercise is associated with sleep in various ways (Morgan, ; Sherrill et al ., ) and that this relationship might change with age (Oudegeest‐Sander et al ., ); however, Buman and King () suggest the cross‐sectional nature of these studies ‘precludes an understanding of the temporal nature of the relationship (i.e. individuals experiencing better sleep may be more inclined or disposed to be more physically active during the day)’.…”
Section: Discussionmentioning
confidence: 99%
“…TST referred to the sum of the minutes scored as sleeping from sleep onset to the end of the sleep episode . Sleep efficiency was calculated as TST/time in bed × 100 (%) …”
Section: Methodsmentioning
confidence: 99%